Особливості застосування методу редукції при виконанні аналітичних вимірювань - Захаров, О. І. (ХНУРЕ, 2025)
The problem of analytical measurements uncertainty evaluation in which the results of measurements of several input quantities are dependent is considered. It is proposed to use the method of reduction, which not only takes into account the correlation between these quantities, but also allows obtaining unbiased estimates of the measurand and its uncertainty for a nonlinear model equation. A procedure for measurement uncertainty evaluation for this case is given.
Keywords: метод редукції; аналітичні вимірювання